Aggregating Information by Voting: The Wisdom of the Experts versus the Wisdom of the Masses - McMurray, Joseph C. (Review of Economic Studies, 2013)
This paper analyzes participation and information aggregation in a common-value election with continuous private signals. In equilibrium, some citizens ignore their private information and abstain from voting, in deference to those with higher-quality signals. Even as the number of highly-informed peers grows large, however, citizens with only moderate expertise continue voting, so that voter participation remains at realistic levels (e.g. 50 % or 60%, for simple examples). The precise level of voter turnout, along with the margin of victory, are determined by the distribution of expertise. Improving a voter’s information makes her more willing to vote, consistent with a growing body of empirical evidence, but makes her peers more willing to abstain, providing a new explanation for various empirical patterns of voting. Equilibrium participation is optimal, even though the marginal voter may have very little (e.g. below-average) expertise, and even though non-voters’information is not utilized.